SOCIALIZATION AND TRAINING IN THE PRODUCTION OF BIOETANOL FROM SUGAR CANE IN LUBUK RUMBAI VILLAGE, RUPIT DISTRICT, MUSI RAWAS UTARA DISTRICT - Endang Lovisia; Yaspin Yolanda (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
This community service activity was carried out in Lubuk Rumbai Village, Rupit District, Musi Rawas Regency, targeting the people of Lubuk Rumbai Village. Most of the people of Lubuk Rumbai Village earn their living as farmers or planters, therefore it is considered very appropriate for lecturers to provide community service in Lubuk Rumbai Village. Considering the large number of sugar cane plants in the area. TIM invites local communities to process sugar cane plants in the form of molasses into bioethanol fuel. The local community's lack of knowledge and skills regarding the use of sugar cane molasses has made TIM interested in applying appropriate technology to utilize sugar cane molasses as an alternative energy source, namely bioethanol. With the presence of bioethanol, it is hoped that people will no longer depend on fossil energy considering that energy supplies are currently decreasing. Apart from that, when compared to energy from fossils, the use of bioethanol is more environmentally friendly because it comes from biological material. The method that TIM uses is the method of socialization and training on how to make bioethanol from sugar cane molasses. Based on the results of the skills questionnaire given by TIM to 15 respondents, it was found that 80% of the community were satisfied with this training activity.